ISOLATION OF STAPHYLOCOCUS AUREUS AND COAGULASE NEGATIVE STAPHYLOCOCCIFORM BOVINE SUBCLINICAL MASTITIS AND THEIR IMPACT ON THE CHEMICAL COMPONENTS OF MILK - Ali A. Al-Iedani (Basrah Journal of Veterinary Research)
This study was conducted to isolate Staphylococcus aureus and Coagulase Negative Staphylococci (CNS) from bovine subclinical mastitis cases and study their effect on chemical composition of milk. A total of 152 milk samples were collected from apparently normal cows from Basrah province, subclinical mastitis (SCM) was detected in 51.97% of tested samples by using California mastitis test (CMT). Staphylococcus aureus and CNS were isolated from 20.25% and 16.45% cases of tested SCM respectively. The affected samples with SCM have high concentrations of fat and protein, the difference from normal samples was statistically highly significant (P ˂0.001) for fat; lactose was lower in affected samples. The pH of affected samples was higher than that of normal, however, pH of samples containing S. aureus was the highest (7.8375) and the difference was statistically significant (P˂ 0.05). Antimicrobial susceptibility assay revealed that all isolates were susceptible to chloramphenicol, ciprofloxacin, gentamycin and vancomycin. However, the resistance to oxacillin and penicillin exhibited by CNS and S. aureus were 76.9%, 84.6%, 62.5% and 68.75% respectively. It have been concluded that, subclinical mastitis caused by Staphylococci(in particular S. aureus) which carried resistance to antibioticsused in human medicine represents a big problem.However, the changes caused by S. aureus and other staphylococci in pH and chemical composition of mastitic milk may reduce the shelf life and processing of the products.